2016
DOI: 10.1016/j.cell.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Transient RNA-DNA Hybrids Are Required for Efficient Double-Strand Break Repair

Abstract: RNA-DNA hybrids are a major internal cause of DNA damage within cells, and their degradation by RNase H enzymes is important for maintaining genomic stability. Here, we identified an unexpected role for RNA-DNA hybrids and RNase H enzymes in DNA repair. Using a site-specific DNA double-strand break (DSB) system in Schizosaccharomyces pombe, we showed that RNA-DNA hybrids form as part of the homologous-recombination (HR)-mediated DSB repair process and that RNase H enzymes are essential for their degradation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

37
344
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(402 citation statements)
references
References 45 publications
37
344
4
Order By: Relevance
“…For instance, contrary to what was proposed before [16,23], we could not detect significant R-loop formation either over heterochromatin repeats at centromeres or over gene terminator regions in fission yeast. Although we confirmed that the S9.6 antibody immuno-precipitates RNA species associated with centromeric repeats and terminator regions (Figs.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…For instance, contrary to what was proposed before [16,23], we could not detect significant R-loop formation either over heterochromatin repeats at centromeres or over gene terminator regions in fission yeast. Although we confirmed that the S9.6 antibody immuno-precipitates RNA species associated with centromeric repeats and terminator regions (Figs.…”
Section: Discussioncontrasting
confidence: 99%
“…The first map was generated by DRIP-seq and as a result was not stranded and had low resolution [16]. The second map was made using a ChIP-exo approach to increase resolution, but it only provided a map of R-loops in cells lacking RNase H activity ( rnh1Δrnh201Δ cells) and the sensitivity of the signals to RNase H was not controlled [23]. The maps produced here are stranded and have high resolution, and the sensitivity of the signals to in vivo RNase H level manipulations has been validated.…”
Section: Discussionmentioning
confidence: 99%
“…6a). Considering that RNA-DNA hybrids have recently been shown to form at DNA breaks, Polθ-helicase dissociation of these structures may also contribute to DSB repair (27).…”
Section: Discussionmentioning
confidence: 99%
“…For example, R-loops have long been associated with replicative stress and genome instability, whereas more recent work indicates that RNA-DNA hybrids can also promote DNA repair by mechanisms that remain to be elucidated (23)(24)(25)(26)(27). Considering the importance of RNA-DNA structures in DNA repair and genome instability, we proceeded to examine whether Polθ-helicase unwinds RNA-DNA duplexes with similar efficiency.…”
Section: Polθ-helicase Unwinds Dna In An Atp and Datp Dependent Mannermentioning
confidence: 99%
“…As discussed in this review, emerging evidence indicates that there is a repair process that occurs in regions open for transcription interfacing transcriptional arrest and repair, akin to the distinction between transcription coupled repair and global genome repair at UV photoproducts. An emerging topic in the field of DNA repair is the contribution of transcription and RNA to the repair process [34][35][36]. In particular, DNA-RNA hybrids or R-loops can present a source of DNA damage but equally can profoundly influence the repair process.…”
mentioning
confidence: 99%